Comparison between Graded Crushed Gravel Filter and Textile Filter using Statistical Analysis - Alhaddad, Amer Hasan; Naji, Rusul Latteef (Al-Nahrain Journal for Engineering Sciences, 2019)
Many researchers have applied several experiments and research studies by developing criteria’s design of drainage to improve the drainage process, and to show that the filters plays an important role to improve and maintain the drainage system from being blocked due to siltation. There are several types of filters, including granular mineral materials and organic materials, the other filter that was used is made from a special fabric material such as paper, burlap, or special fabric textile material. The objective of this study is to evaluate the performance of textile filters, and if it is desirable and suitable for Iraqi soil using statistical analysis. This study was conducted in the laboratory using sand tank model and two types of filters (graded crushed gravel and textile) with two types of soil (sandy soil and loamy soil) to compare and evaluate the hydraulic performance and the efficiency of utilizing textile filter instead of graded crushed gravel filter in drainage systems using statistical analysis methods. These statistical analysis show that there was a good agreement between measured and theoretical values of entrance resistance when using the two filters in sandy soil. On the other hand, the results showed that there was a weak performance when textile filters in were used in heavy soil (loamy soil) due to the high value of root mean square error (RMSE) and low value of agreement index (d). The results of statistical analysis show that the textile filter is desirable and suitable for Iraqi soil especially for sandy soil due to low entrance resistance of flow compared to loamy soil.